Impact of COVID-19 Lockdown on Air Pollutant Emissions in Port Regions. Scoping Review (Epidemiology, Biostatistics, and Public Health, 2024)
Background: This scoping review, a comprehensive effort to map and synthesize evidence, sheds light on the impacts of the COVID-19 lockdown on air pollutant emissions in port regions.Methods: It was conducted based on the Joanna Briggs Institute Manual and the PRISMA-ScR recommendations. An extensive literature search was undertaken to identify any scientific study or report comparing greenhouse gas emissions before and after the COVID-19 pandemic in maritime port regions.Results: Nine observational studies conducted in ports of five countries were identified, 75% using the Automatic Identification System (AIS) as a measurement system for pollutant emissions. When comparing the same period before and after the pandemic lockdown, the results of seven studies identified a reduction of up to 63% in the emission of CO2, NO2, CO, HC, NOx, SOx, HC, PM2.5, and PM10, and an increase of 37% in O3. Additionally, two studies reported increased pollutant emissions, explained by ship congestion in ports.Conclusion: These findings indicate an important reduction in pollutant and particulate matter emissions during the port activity restrictions imposed by the COVID-19 pandemic worldwide compared to the same period in 2019. This reduction was mainly attributed to the reduced activity of vessels and vehicle circulation. These findings can provide valid scientific evidence to support the air pollution control policies in coastal cities and assist in ensuring sustainable practices, environmental regulations, and monitoring for mitigating air pollution in port regions.
Keywords: Port activities; Atmospheric pollutants; COVID-19; Scoping review